2007
DOI: 10.1007/s00262-007-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a dendritic cell maturation marker CD83 on tumor cells from lung cancer patients and several human tumor cell lines: is there a biological meaning behind it?

Abstract: The present paper shows, for the first time, the membrane expression of the dendritic cell maturation marker CD83 on tumor cells from lung cancer patients. CD83 was also detected on freshly cultured fibroblast-like cells from these tissues and on several adherent human tumor cell lines (lung adenocarcinomas P9, A459 and A549, melanomas A375 and C81-61, breast adenocarcinomas SKBR-3 and MCF-7 and colon carcinoma AR42-J), but not in the non-adherent MOT leukemia cell line. CD83 may have immunosuppressive propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
10
1
4
Order By: Relevance
“…Other immune system cell components and a greater number of cases might explain this matter. It has been postulated that the increased frequency of LCs into the tumor can be explained by tumor growth that causes local tissue damage and, consequently, the recruitment of inflammatory cells to the tumor site (10). In this study, no significant difference was observed between CD1a-positive LCs and the degree of inflammation response.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Other immune system cell components and a greater number of cases might explain this matter. It has been postulated that the increased frequency of LCs into the tumor can be explained by tumor growth that causes local tissue damage and, consequently, the recruitment of inflammatory cells to the tumor site (10). In this study, no significant difference was observed between CD1a-positive LCs and the degree of inflammation response.…”
Section: Discussioncontrasting
confidence: 57%
“…Langerhans cells (LCs), an immature dendritic cell type that resides in epithelial tissue, are believed to play a fundamental role in the presentation of tumor antigens to T cells inside lymph nodes, producing an antitumor response (4)(5)(6)(7). An increase in the number of these cells has been associated with a better prognosis of different tumors (8)(9)(10)(11)(12)(13), although their role in odontogenic tumors has not yet been established (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Little is known about the participation of LCs in odontogenic tumors, as the presence of these cells has been merely mentioned based almost exclusively on case reports and not appropriately discussed by previous studies (14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…CD83 is a transmembrane protein, mainly known as a marker of mDCs [8], although it is also expressed in activated B [9] and T cells [10], neutrophils [11], thymic epithelial cells [12], and tumor cells [13]. CD83 also has a soluble isoform that can be detected in the serum [14].…”
Section: Introductionmentioning
confidence: 99%
“…Foi confirmada a expressão de CD83, que já havia sido descrita nessa linhagem em trabalho do nosso grupo (Baleeiro, 2008a). Num outro trabalho também de nosso grupo, ficou demonstrado que a molécula CD83 quando liberada por células tumorais, apresentava possível propriedade imunossupressora, visto que, quando havia o bloqueio do CD83 solúvel com o uso de anticorpos, essa característica imunossupressora do sobrenadante de cultura de células tumorais era perdida (Baleeiro, 2008b).…”
Section: Imunohistoquímicaunclassified